Pemahaman Demokrasi melalui Pembelajaran PPKn dalam Pengembangan Civic Disposition Siswa Kelas VII: Studi Kasus SMP Negeri 3 Binjai Tahun Pelajaran 2023/2024 - Fadillah Melani Putri; Liber Siagian (Departement of Mathematics Education, 2024)
The aim of this research is to explore the understanding of democracy and examine the development of Civic Disposition among seventh-grade students at SMP Negeri 3 Binjai during the 2023/2024 academic year. This qualitative research involves observations, interviews with Civics (PPKn) teachers and class commissioners, as well as document analysis. The subjects of this research are teachers, class commissioners, and student council (OSIS) members. This study uses Miles and Hubberman's (1994) data analysis technique, which consists of three parts: data reduction, data display, and data verification. The results show that understanding the concept of democracy through Civics education contributes to the formation of students' Civic Disposition. Democratic participation experiences, such as elections and class commissioner elections, provide a strong foundation for developing students' democratic attitudes and skills. The role of teachers in guiding students and training programs, such as leadership training, also support students' participatory experiences. Despite the challenges, understanding the concept of democracy helps students overcome obstacles and strengthens their Civic Disposition, making them active and responsible citizens in a democratic society.